Nuclear and Nucleolar Localization of Bovine Adenovirus-3 Protein V - Zhao, Xin; Tikoo, Suresh K. (Frontiers in Microbiology, 2021)
ABSTRACT The L2 region of bovine adenovirus-3 (BAdV-3) encodes a Mastadenovirus genus specific protein designated pV, which appear important for the production of progeny virus. Here, we demonstrate that BAdV-3 pV expressed as 55 kDa protein localizes to nucleus and specifically targets nucleolus of the infected cells. Analysis of deletion mutants of pV suggested that amino acids 81-120, 190-210 and 380-389 act as multiple nuclear localization signals (NLS), which also appear to serve as the binding sites for importin α-3 protein, a member of importin / nuclear import receptor pathway. Moreover, pV amino acids 21-50 and 380-389 appear to act as nucleolar localization signals (NoLs). Interestingly, amino acids 380-389 appear to act both as NLS and as NoLS. Presence of either NoLS is essential for the production of infectious progeny virion as deletion of both NoLs are lethal for the production of infectious BAdV-3. Analysis of mutant BAV.pVd1d3 (isolated in pV completing CRL cells) containing deletion / mutation of both NoLS in non-complementing CRL cells not only revealed the altered intracellular localization of mutant pV but also reduced expression of some late proteins. However, it does not appear to affect the incorporation of viral proteins including mutant pV in BAV.pVd1d3 virions. Further, analysis of CsCl purified BAV.pVd1d3 suggested the presence of thermo-labile virions with disrupted capsids, which appear to affect the infectivity of the progeny virions. Our results suggest that pV contains overlapping and non-overlapping NoLS/NLS. Moreover, presence of both NoLS appear essential for the production of stable and infectious progeny BAV.pVd1d3 virions.